Anion binding by multidentate Lewis acids: a DFT study - Aldridge, S; Fallis, I; Howard, S (2001)
Density functional studies of model tribora-macrocyclic Lewis acids indicate extremely strong binding of the methyl anion, which in some cases exceeds that of B(C 6F 5) 3. In addition anion selectivity for the fluoride ion is implied by binding energies ca. 200 kJ mol -1 greater than those of other halides.